EVALUATION OF ROCK PHOSPHATE SOLUBILIZATION CAPACITY BY ISOLATED STRAINS AND THEIR EFFECT ON MUNGBEAN - M. B. Hossain; M. A. Sattar; M. M. Islam; M. A. Hakim (Journal of Animal and Plant Sciences, 2013)
We determined the degree of P-solubilization using phosphate solubilizing isolates and their effect on growth and yield of mungbean by both laboratory and pot experiments. For phosphate solubilization study, thirty four isolates including control was tested the degree of phosphate solubilization using rock phosphate. In pot condition, four levels of P (0, 20, 40 and 60 kg P ha-1) were tested with seven effective phosphate solubilizers on mungbean. Each experiment was laid out in a complete randomized design with four replications. The effective phosphate solubilizing isolate was obtained from rice rhizosphere soil at Old Brahmaputra Floodplain (AEZ-9). Phosphorus solubilization ranged from 0.21 to 7.34 mg P L-1 in I21 and I16, respectively. Inoculation of phosphate solubilizing isolates considerably enhanced the nodulation and yield of mungbean while the effect was more pronounced when they were applied with phosphatic fertilizer compared to un-inoculated with no phosphatic fertilizer. The highest nodule number (24.00 and 96.17 per plant) and dry weight (40.00 and 84.75 mg per plant) was produced by I1 and I5 at Bogra and I7 at Pabna, respectively. Among the phosphorus levels, 20 and 60 kg P ha-1 showed the maximum seed yield of mungbean at Pabna and Bogra. Based on the results, it may be concluded that phosphorus @ 20 and 60 kg P ha-1 along with I4 and I1 isolates were the best treatments for increasing mungbean yield at Pabna and Bogra, respectively. However, a comprehensive approach to employ the isolates in mungbean should be carried out to explore the hidden potential of isolates and to promote the growth and yield of mungbean under field conditions.
Keywords: Mungbean; agroecological zones; isolates; phosphate solubilization; nodulation and yield